Ethical guidelines for the documentation of árbediehtu, Sami traditional knowledge. : Working with Traditional Knowledge: Communities, Institutions, Information Systems, Law and Ethics. Writings from the Árbediehtu Pilot Project on Documentation and Protection of Sami Traditional Knowledge. - Jonsson, Asa Nordin (Sámi allaskuvla / Sámi University College, 2011)
Documentation of the traditional knowledge of indigenous peoples is becoming increasingly common; one reason for this is that such knowledge is becoming ever weaker and even in some cases disappearing. This is partly due to the increasing influence of Western ways of life on indigenous communities and the passing away of the older generation, taking with them a great deal of the knowledge. Indigenous peoples themselves are today often in the forefront in demanding that traditional knowledge be collected, preserved and passed on to the younger generations, and the indigenous peoples also want to be primarily responsible for such work (Burgess 1999). Traditional knowledge ranges from the limited traditions of specific families or areas to the more comprehensive traditions which the Sami people have in common, regardless of district affiliation. A Sami tradition can be very local in character and thus only apply to a small geographic area. Other Sami may not be familiar with the tradition, because they come from a locality where different customs developed (Gaup 2008). A myriad of different traditions is an expression of cultural wealth, and is also a reflection of how knowledge is adapted to the distinct ecological niches or environments found in Sápmi (Samiland). The aim of the present article is an attempt to create guidelines for how árbediehtu (Sami traditional knowledge) should be documented without exploiting the culture. The article must therefore be regarded as a contribution to an ongoing discussion.